Power System Topology Verification with Use of Reduced Unbalance Indices - Okon, T.; Wilkosz, K. (Elektronika ir Elektrotechnika, 2014)
Knowledge about a correct topology model is required for monitoring, control and analyses of a power system. There are many papers which deal with the examination of correctness of the mentioned model. Among approaches to solving a problem of examination of that correctness there is one assuming utilization of raw analogue measurement data. That approach does not require complex numerical computations. It is utilized in the paper. In the paper, a next stage of investigation on topology verification based on utilization of so-called unbalance indices is presented. In that stage, the original idea of reduced unbalance indices, being a modification of the earlier-mentioned unbalance indices, is introduced. Utilization of the new unbalance indices increases possibility of taking verification decision when there are multiple topology errors and decreases sensitivity of topology verification to a lack of a full set of measurement data. The topology verification can be performed locally (e.g. in a substation what is often now considered) as it is in the case of earlier-defined unbalance indices. Utilization of the proposed method is shown on an example of topology verification of the IEEE 14-bus test system. DOI: http://dx.doi.org/10.5755/j01.eee.20.9.8708